Analysis of Olympic education theoretical readiness of future physical culture teachers - A.A. Bondar (Physical Education of Students)
Purpose: analysis of Olympic knowledge system in future physical culture teachers. Material: in the research 180 4 year students of physical culture faculties participated. Results: it was found that students’ theoretical knowledge level in the sphere of Olympic movement corresponds to low. It was confirmed that system of Olympic knowledge is an integral part of future physical culture teachers’ readiness for Olympic education of schoolchildren. It was found that in the process of knowledge formation in students it is necessary to consider theoretical material on Olympic education, acting academic programs for pupils of comprehensive educational establishments. Conclusions: students have low level of knowledge in sphere of Olympic movement (general indicator was 57.4%). It weakens effectiveness of skills, knowledge and motivation’s formation in realization of schoolchildren’s Olympic education.